Phloretin loaded chitosan nanoparticles enhance the antioxidants and apoptotic mechanisms in DMBA induced experimental carcinogenesis. (1st August 2019) - Mariadoss, Arokia Vijaya Anand; Vinayagam, Ramachandran; Xu, Baojun; Venkatachalam, Karthikkumar; Sankaran, Vijayalakshmi; Vijayakumar, Shalini; Bakthavatsalam, Sandya Rani; A Mohamed, Sadiq; David, Ernest
Abstract: The main aim of this study was to investigate the effects of phloretin loaded chitosan nanoparticles (PhCsNPs) on 7, 12-dimethylbenz[a]anthracene (DMBA) induced experimental cancer in hamsters. Oral squamous cell carcinoma (OSCC) was induced in male golden Syrian hamsters by painting with 0.5% DMBA three times a week for 14 weeks. Varying concentration of PhCsNPs (5, 10, and 20 mg/kg b.wt.) was orally administered on alternative days to evaluate the optimum dose. The experiment design was terminated at the end of the 14th week. The development of OSCC was confirmed by histopathological and biochemical analysis (lipid peroxidation, antioxidant profile, and detoxification enzymes) in plasma, erythrocyte, buccal, and liver tissues. Significant increases in oxidation and lipid peroxidation were noticed in DMBA-painted hamsters. Oral administration of PhCsNPs in various doses on alternate days reversed the deleterious effects induced by DMBA. In addition, immunoblot analyses of PhCsNPs treatment enhanced the release of Bcl-2 associated X protein (Bax), cytochrome c, caspase-3, 9 and suppressed the B-cell lymphoma 2 (Bcl-2) expression, which the use of PhCsNPs for mitochondrial-mediated apoptosis. These findings suggest biofabricated PhCsNPs may act as a potent antioxidant and anti-carcinogenic in DMBA induced oral cancer in experimental animals. Graphical abstract: Image 1 Highlights: Nanochemoprevention of phloretin loaded nanoparticles was characterized for the first time. PhCsNPs exhibited significant antioxidants and detoxification effects in experimental carcinogenesis. PhCsNPs treatment significantly reduced the tumor volume and neoplastic changes. PhCsNPs enhance the mitochondrial-mediated apoptosis.